The role of police in conducting wellness checks: Insight from a study of police data. (4th July 2022) - Pearce, Jeremy; Simpson, Rylan
ABSTRACT: The role of police in conducting wellness checks has received considerable public attention in Canada in recent years. Drawing upon data from both the computer-aided dispatch and records management systems of a mid-size police agency in Western Canada, we identify and then descriptively assess all wellness checks conducted in 2020 (N = 1, 114 events). As part of our exploration, we explore the nature of these events, the characteristics of those involved, and the responses of the police. Our results reveal a series of patterns regarding the characteristics and outcomes of these events, including by 'official' versus 'unofficial' status. Our results also shed insight into the challenges of using police data for these kinds of research questions. By providing researchers, practitioners, and policymakers with an empirical analysis of wellness checks, we hope to contribute to evidence-based decision-making about these events moving forward.